The Legal Power of Informed Consent as A Valid Evidence in Cases of Alleged Malpractice in Terms of Civil Law - Siti Sundari; Saritua Silitonga; Annisa Danti Avrilia Ningrum (IHSA Institute, 2022)
Patients have rights that must be fulfilled when informed consent. Patient information rights are often ignored. There are at least two kinds of information, namely: first, the risks and complications that may occur, and the prognosis for the actions taken. Providing clear information at the time of informed consent will provide a sense of security and for the patient will understand the actions during the rehabilitation period. A medical action is an action that is full of risks. In legal norms any medical action that results in harm to a patient can be called medical malpractice if it fulfills certain elements in both civil and criminal law. Based on the above background, the problem is how the function of informed consent in evidence in court is related to efforts to find the truth and how is the strength of proving informed consent for judges against alleged malpractice in terms of civil law. For this purpose, research was carried out using a normative juridical approach, the research specifications used were descriptive analytical, the data used in this study were secondary data, namely data obtained through library research. The data technique used is literature. The analysis used is normative qualitative. Based on the results of the analysis of the patient's rights as Article 45 paragraph 1 of Law Number 29 of 2004 concerning Medical Practice says that the operation must obtain the patient's consent, If the patient's condition is an emergency, then the approval of the family. If it is not possible, the operation can be carried out by the hospital authority, Article 56 paragraph (1) of Law Number 36 of 2009 concerning Health states that everyone has the right to accept or reject part or all of the relief measures that will be given to him after receiving and understanding information regarding the action is complete. And based on Article 45 paragraph (3) of Law no. 29 of 2004 concerning Medical Practice explains that risks, complications and prognosis must only be given before surgery. So that normatively informed consent has a legal position as evidence of letters and instructions in cases of malpractice. However, this evidence must be supported by other evidence, such as expert testimony, but if it is related to the teaching of the law, the evidence must still be adjusted to the requirements of the evidence, namely: 1) Allowed by law, 2) Reability, 3) Necessity, and 4) Relevance. Thus, the value of the power of proving informed consent is not fully binding on the judge but depends on the conviction and accuracy of the judge.